FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG - Arga Dewangga; Herry Laksito (Diponegoro Journal of Accounting, 2015)
Timeliness of financial reporting is important to all user to make decision based from information in the financial report. This study aimed to examine the effect of profitability, solvency, the size of the company, the audit opinion, the life of the company and the auditor industry specialization to the audit report lag.The population in this study are all companies in all areas of business that have been listing on the Stock Exchange in the year 2011-2013, the sampling method used in this research is purposive sampling. The number of samples in the study were 49 companies, namely the financial sector or financial companies.The test results demonstrate the audit opinion and firm age affects the audit report lag while the other independent variables have no significant effect on the audit report lag.